(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
The incidence rate and mortality of coronary artery disease is obviously higher in men than in women, which may be related to the influence of serum testosterone. This cross-sectional study was conducted at Department of Laboratory Medicine in collaboration with Department of Cardiology, BSMMU and National Institute of Cardiovascular Diseases (NICVD), Dhaka from March 2020 to February 2021 to investigate the association of serum testosterone with coronary artery disease in young adult males in Bangladesh. Total 110 subjects from inpatient Department of Cardiology were enrolled, 60 were CAD patients and 50 were Normal Coronaries according to coronary angiography report. In this study, 60 patients with coronary artery disease were compared with 50 normal coronary subjects. Mean age in CAD group and normal coronaries was 37.72±2.73 and 37.48±2.54 years respectively. Hypertension, diabetes mellitus and dyslipidemia were significantly higher in CAD group. Total testosterone levels of CAD were significantly lower than those of normal coronaries (2.11±0.81ng/ml vs 2.94±0.78ng/ml). Among 60 CAD patients, 10 patients had single vessel disease, 17 patients had double vessel disease and 33 patients had triple vessel disease. There was significant association between the level of total testosterone and the number of affected vessels within CAD group (p=0.1). This study also showed that total testosterone level was negatively correlated with Gensini score. Serum total testosterone was significantly lower in patients with CAD compared to normal coronaries. Patients with lower total testosterone levels had higher Gensini score. Low level of total testosterone may be related to the develop- ment of coronary artery disease. BSMMU J 2021; 14(3): 67-73